2002
DOI: 10.1046/j.1439-0418.2002.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some characters on the population growth of mite Varroa jacobsoni in Apis mellifera L colonies and results of a bi‐directional selection

Abstract: Two lines of honey bees (Apis mellifera ligustica) were selectively propagated by instrumental insemination using the population growth of the Varroa mite as a criteria. Different infestation rates are at least partially genetic since selection produced significant bi‐directional differences between lines over a period of three subsequent generations. There was no correlation between several behavioural and physiological characteristics which are potentially associated with Varroa resistance (hygienic behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…The annual average r values for most years in this study (r ϭ 0.105Ð 0.214 wk Ϫ1 ) were similar to the values from other studies (r ϭ 0.108 Ð 0.236 wk Ϫ1 ) (Thrybom and Fries 1991;Calatayud andVerdu 1993, 1995;Kraus and Page 1995;Marcangeli et al 1995;Branco et al 1999;Vandame et al 2000;Lodesani et al 2002). However, the three lowest values (r ϭ Ϫ0.008 Ð 0.047 wk Ϫ1 ) were well below the lowest growth rates reported elsewhere, and they occurred during a period (1998 Ð 2000) of below normal rainfall in Louisiana.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The annual average r values for most years in this study (r ϭ 0.105Ð 0.214 wk Ϫ1 ) were similar to the values from other studies (r ϭ 0.108 Ð 0.236 wk Ϫ1 ) (Thrybom and Fries 1991;Calatayud andVerdu 1993, 1995;Kraus and Page 1995;Marcangeli et al 1995;Branco et al 1999;Vandame et al 2000;Lodesani et al 2002). However, the three lowest values (r ϭ Ϫ0.008 Ð 0.047 wk Ϫ1 ) were well below the lowest growth rates reported elsewhere, and they occurred during a period (1998 Ð 2000) of below normal rainfall in Louisiana.…”
Section: Discussionsupporting
confidence: 90%
“…However, the three lowest values (r ϭ Ϫ0.008 Ð 0.047 wk Ϫ1 ) were well below the lowest growth rates reported elsewhere, and they occurred during a period (1998 Ð 2000) of below normal rainfall in Louisiana. At least one other study has noted differences in growth of mite populations among years in the same location (Lodesani et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most of these parameters are mutually influenced and part of complex multifactorial interactions. Some authors tried to extract the most important factors by the use of multifactorial analyses (Arechavaleta-Velasco and Guzman-Novoa, 2001; Harris et al, 2003;Lodesani et al, 2002). They confirmed significant correlations between the amount of brood and/or the fertility of the mites and population growth; however, prediction to what extent a starting mite population in the spring will increase until autumn is still not possible.…”
Section: Population Dynamicsmentioning
confidence: 99%
“…Other studies have not found this correlation to be clear and significant (Lodensani et al, 2002;Locke and Fries, 2011), or have found that other factors, such as mite reproduction, better explain the variability in mite infestation levels between colonies (Ritter and de Jong, 1984;Rosenkranz and Engels, 1994;Harris and Harbo, 1999;Martin and Medina, 2004;Mondragon et al, 2005;Locke and Fries, 2011). Moreover, the validity of using the proportion of injured mites as a criterion to select bees for mite resistance has been questioned (Rosenkranz et al, 1997;Bienefeld et al, 1999), because a considerable number of injured mites found on hive bottom boards may not have been damaged by the bees.…”
Section: Grooming Behavior At the Colony Levelmentioning
confidence: 99%
“…The degree to which grooming behavior is affected by genetic effects is still not well known, and results of experiments are contradictory. For example, Moretto et al (1993) calculated an h 2 value of 0.71 for this behavior; however, later studies found low h 2 values for this trait Lodensani et al, 2002;Stanimirovic et al, 2010). It is possible that these contradictory results are a consequence of differences in the accuracy with which different assays assess grooming behavior.…”
Section: Genetic Basis Of Grooming Behaviormentioning
confidence: 99%